Sensipal Plush: Sensory Therapy for State Anxiety in Emerging Adulthood with Social Anxiety - Eleonora, Erica; Rania, Rania; Jonathan, Jonathan; Sandjaja, Meilani; Eunike , Prisca (Journal Research of Social Science, Economics, and Management, 2026)
Social anxiety disorder is highly prevalent during emerging adulthood (18-25 years). This condition triggers an emotional surge of state anxiety directly when individuals face pressure in social situations. This study presents the design and tests the effectiveness of SensiPal, a Huggable Sensory Therapy Plush prototype integrating Deep Pressure Therapy (DPT), tactile stimulation, and white noise to reduce state anxiety in social situations. Utilizing a one-group pretest-posttest quasi-experimental design, this field experiment involved 30 participants in a public location. Anxiety levels were measured using the State-Trait Anxiety Inventory State Form (STAI-S). Paired Sample t-Test results demonstrated a significant decrease in the average state anxiety score from 21.20 to 15.57 following a 12-minute SensiPal intervention. An effect size of 1.455 indicates a very strong intervention impact. In conclusion, SensiPal is proven effective as a portable coping mechanism supporting immediate independent emotion regulation (self-soothing) in stressful social settings.